Control interno de inventarios de materia prima en la empresa ALTEC S.A. en la ciudad de Babahoyo - Alburqueque Guerrero, Ernesto Adolfo (2020)
Inventories represent one of the areas of acceptance within a company, since each of the goods that exist for sale can be established and thus obtain the income that any organization requires. In this study, the company ALTEC S.A. It is an entity that offers window products to the general public, however it presents a problem: the lack of internal control of its inventories, this has generated difficulties in the accounting area, since many of its products are not delivered on time due to the poor control of activities, facilitating the client to give up buying and therefore there is a loss; that is why, once the problem was identified, the case study was developed, made up of each of the arguments that are valid for reading comprehension, and also contributed to the understanding of the central theme of inquiry; The research technique that was used in the process was surveys, since it is the most effective method of collecting information in the investigative process. Consequently, a manual was developed so that the employees in charge can carry out their functions in a practical and simple way, keeping control of the inventories.